The effects of prophylactic intravenous injection of rhBNP on prognosis in patients with STEMI undergoing PPCI - Liu, Yanjun; Xie, Chunqiao; Hou, Yiyong; Li, Kefei; Wang, Qi; Lin, Lin; Tang, Min; Yang, Peng; Wu, Jiakuan (Cellular and Molecular Biology, 2023)
This experiment was carried out to observe the application value of recombinant human brain natriuretic peptide (rhBNP) in patients with ST-segment elevation myocardial infarction (STEMI) by primary percutaneous coronary intervention (PPCI), to provide reference for the future treatment of STEMI. In this study, we selected STEMI patients who underwent PPCI treatment in our hospital from October 2019 to December 2021 were selected as the study subjects, of which 46 received intravenous injections of rhBNP (research group), and 36 STEMI patients underwent PPCI (control group). There was no difference in clinical efficacy between the two groups (P>0.05). After treatment, high-sensitivity cardiac troponin I (hs-cTnI), creatine kinase-MB (CK-MB) and plasma N-terminal pro-BNP (NT-proBNP) levels decreased in both groups, with the research group lower than the control group; cardiac output (CO), cardiac index (CI) and mean arterial pressure (MAP) of the research group were lower than the control group's (P<0.05). The left ventricular ejection fraction (LVEF) in the research group was higher than that in the control group at 1 week and 1 month after treatment, while left ventricular end-diastolic diameter (LVEDD) and left ventricular end-systolic diameter (LVESD) were lower than those in the control group (P<0.05). There was also no difference in the rate of prognostic risk events between the two groups at 6 months of follow-up (P>0.05). Combining the results of these experiments above, we believe that the intravenous injection of rhBNP in STEMI patients undergoing PPCI treatment can improve cardiac function and promote the recovery of hemodynamics.This experiment was carried out to observe the application value of recombinant human brain natriuretic peptide (rhBNP) in patients with ST-segment elevation myocardial infarction (STEMI) by primary percutaneous coronary intervention (PPCI), to provide reference for the future treatment of STEMI. In this study, we selected STEMI patients who underwent PPCI treatment in our hospital from October 2019 to December 2021 were selected as the study subjects, of which 46 received intravenous injections of rhBNP (research group), and 36 STEMI patients underwent PPCI (control group). There was no difference in clinical efficacy between the two groups (P>0.05). After treatment, high-sensitivity cardiac troponin I (hs-cTnI), creatine kinase-MB (CK-MB) and plasma N-terminal pro-BNP (NT-proBNP) levels decreased in both groups, with the research group lower than the control group; cardiac output (CO), cardiac index (CI) and mean arterial pressure (MAP) of the research group were lower than the control group's (P<0.05). The left ventricular ejection fraction (LVEF) in the research group was higher than that in the control group at 1 week and 1 month after treatment, while left ventricular end-diastolic diameter (LVEDD) and left ventricular end-systolic diameter (LVESD) were lower than those in the control group (P<0.05). There was also no difference in the rate of prognostic risk events between the two groups at 6 months of follow-up (P>0.05). Combining the results of these experiments above, we believe that the intravenous injection of rhBNP in STEMI patients undergoing PPCI treatment can improve cardiac function and promote the recovery of hemodynamics.